Comparative study of pitch estimation for speech and music - Chandrahasan Anandan. (2008)
Pitch of audio signals is used in speech and music synthesis, speech transmission and automatic speaker recognition (ASR). Without pitch, any description of sound signal will not be complete. So pitch estimation becomes an important task in audio processing. Before going into pitch estimation techniques, a sound description of the working principle of ear and speech production of human system are studied.